Moderasi Beragama: Philantropy Ekonomi Islam Melalui Kepatuhan Zakat Hasil Laut di Pesisir Lamongan - Latifah, Eny (Proceedings of Annual Conference for Muslim Scholars, 2023)
The purpose of this study is to determine the extent to which the coastal communities of Lamongan reflect compliance in paying zakat on marine products as a form of Islamic economic philanthropy in reflecting religious moderation. The research method used is descriptive qualitative with the type of case study in the Fisherman's Association of Kranji Village, Paciran District, Lamongan Regency. in the Fishermen Association of Kranji Village, Paciran District, Lamongan Regency. The result of the research is religious moderation, one of which can be realized by Islamic Economic philanthropy carried out by the Lamongan coastal community Compliance in paying zakat on existing marine products is divided into 3 (Three) Types: (1) Zakat is paid with the analogy of Zakat (2.5%).2.5% (2) Zakat is paid with a special calculation (the fishermen themselves determine the calculation on the basis of their income). calculation (calculation determined by the fishermen themselves on the basis of income earned is not (3) Zakat is paid with voluntary calculations (large/small income is always set aside for zakat or alms).